Análise econômica de corredores estruturais de ônibus - Ribeiro, Allyne Rodrigues (2009)
Due to policy of prioritizing public transportation has become more frequent of bus corridors implementation, this work makes the technical, operational and economic analysis of the implementation of this type of enterprise. Initially, in this work was tried to identify the level of service that the transportation system operates and the types of intervention that currently are in use. Based on boarding and alighting flows on stops and collecting operational data to simulate the movement and get the operating speed in the corridor, travel time and number of people who use the service during peak hours. These data were analyzed based on concepts of operational analysis, then, it was carried out economic analysis of the enterprise. The benefits due to reduced travel time and costs of operation, maintenance and implementation were considered along the estimated useful life of 20 years. Had used the methods of net present value (NPV) of cost / benefit ratio (CBR) and Internal Rate of Return (IRR), in order to verify the economic feasibility of the project. The case study was conducted at the bus structural corridor at João Naves de Ávila Avenue, located in the southern city of Uberlândia, Minas Gerais, a Brazilian medium sized city.